Improving Learning Skills in Islamic Education Learning through Demonstration Methods at SD Negeri 1007 Tanjung Baringin - Hasibuan, Ahmad Ripai; Hasibuan, Marni Hotnida; Harahap, Hafni Suryati (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve learning skills in Islamic religious education learning using the Demonstration Method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the Demonstration Method can improve students' learning skills in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle increased to 90.32%. Thus, learning using the demonstration method can be used as an alternative to improve students' learning skills in Islamic religious education learning.